Clinical Observation on Lumbar Muscle Fasciitis Treated by Siling and Tuina Exercise Technique Combined with Kinesiology Tape - Yi DING; Chenchen GUO; Ning WANG; LI Li (康复学报)
Objective:To observe the clinical effect of Siling and Tuina exercise technique combined with kinesiology tape(KT)on lumbar muscle fasciitis and explore the changes of MPF in the frequency domain of surface electromyography, and explain the mechanism of this comprehensive rehabilitation program on the improvement of lumbar muscle fasciitis.Methods:A total of 60 lumbar muscle fasciitis patients treated in the outpatient department of the rehabilitation center of the second affiliated hospital of Shandong University of Traditional Chinese Medicine were collected. The eligible patients were divided into treatment group and control group by random number table method, with 30 cases in each group. The treatment group was treated with Siling and Tuina exercise technique combined with KT, while the control group was only treated with KT.In the suspension state, the patients in the treatment group underwent local meridian stretch and rib rectification, combined with the open and closed chain active movement in the supine position and prone position for 30 minutes. Then the patients in the treatment group received KT, which followed the principle of"improving pain threshold, promoting circulation, and relieving fatigue". The patients were given sticking with shapes of"X"and"claw"KT under appropriate position for 24 hours, once a day. The same KT was performed in the control group. The above two groups were treated once a day, five times for a course of treatment, two days rest between courses, and a total of four courses of treatment. Before and after the treatment, McGill simplified scale was used to assess the changes in pain degree of patients, and the changes in frequency domain index(MPF)in sEMG were used to assess the changes in the fatigue degree of bilateral multifidus muscle and vertical spine muscle. Rehabilitation follow-up was conducted three months after the end of treatment, and the recurrence rate was calculated.Results:After four courses of treatment, the scores of McGill simplified scale of two groups were lower than those before treatment, and the decrease was more obvious in the treatment group than that in the control group(P<0.05);the MPF value of the dorsalis multifidus and erector spinalis were decreased in both groups, but the MPF value decreased more significantly in the treatment group than that in the control group(P<0.05);the recovery rate of the treatment group was higher than that of the control group(P<0.05);the recurrence rate in the treatment group was lower than that in the control group(P<0.05).Conclusion:The treatment of lumbar muscle fasciitis with Siling and Tuina exercise technique combined with KT is more effective than that of simple KT, and the long-term effect is better than that of simple KT.This comprehensive rehabilitation program has the advantages of simple operation and low recurrence rate, and is worthy of clinical promotion and application.